Effectiveness of respite care in supporting informal caregivers of persons with dementia: a systematic review. (1st June 2016) - Vandepitte, Sophie; Van Den Noortgate, Nele; Putman, Koen; Verhaeghe, Sofie; Verdonck, Caroline; Annemans, Lieven
Abstract : Objective: Supporting informal caregivers of persons with dementia is considered to be an effective strategy for improving the well‐being of caregivers and care recipients and for delaying nursing home placement. Although considerable research has been conducted to investigate the effectiveness of psychoeducational interventions, cognitive behavioral therapy, and occupational therapy, research into the effectiveness of respite care is rare. This systematic review aims to investigate the effectiveness of different types of respite care in supporting informal caregivers of persons with dementia. Methods: A systematic literature search was conducted using Web of Science and PubMed, and the Quality Assessment Tool for Quantitative Studies was used to assess the methodological quality. Randomized controlled trials, quasi‐experimental studies, pretest–posttest studies without a control group, and cohort studies were included. Results: Seventeen papers met the inclusion criteria. Day care services are effective in decreasing caregiver burden and behavioral problems in persons with dementia, but they also accelerate time to nursing home admission. The results of temporary residential admission are rather mixed and show unexpected adverse effects on both caregivers and care recipients. High‐quality comparable evidence on community‐based respite care is still lacking, although earlier qualitative evidence indicated promising results. Conclusion: Unlike in previous reviews, we were able to draw some conclusions about the effectiveness of some types of respite care. There is nonetheless still a need for new intervention studies measuring the impact of respite care, especially in‐home respite care programs, on the caregiver, the care recipient, and health care resource utilization. Copyright © 2016 John Wiley & Sons, Ltd.